Olah Kata Sosio-Kultural (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to describe the phenomenon of word processing which has socio-cultural meaning. This type of research is qualitative research. Qualitative research is research used to obtain more in-depth data, namely data that contains meaning. The meaning in question is the actual data in the form of words, sentences and discourse. The data in this research are words, phrases, sentences written by social media users which imply socio-cultural meaning. Data collection techniques in this research are library techniques and note-taking techniques. Library technique is a data collection technique by examining books and journal articles that are related to the problem being solved. The note technique is a technique for noting several forms that are relevant for research on written language use. The data analysis technique in research is descriptive analysis through the steps of identifying data, classifying data, presenting data, and drawing conclusions. As a result of this research, the researcher found five examples of socio-cultural words, including: 1) Black skin, curly hair, I'm Papuan Bae sonde bae land of Timor lebe bae 3) Jogja is special, the country is special, the people are special, Bali Island Attractive Gods, Ama Mawolo, Ina Marawi.